2015
DOI: 10.1080/02687038.2015.1111995
|View full text |Cite
|
Sign up to set email alerts
|

Assessing syntactic deficits in Chinese Broca’s aphasia using theNorthwestern Assessment of Verbs and Sentences-Chinese (NAVS-C)

Abstract: Background English-speaking patients with Broca's aphasia and agrammatism evince difficulty with complex grammatical structures, including verbs and sentences. A few studies have found similar patterns among Chinese-speaking patients with broca's aphasia, despite structural differences between these two languages. However, no studies have explicitly examined verb properties, including the number and optionality of arguments (participant roles) selected by the verb, and only a few studies have examined sentence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…Over the past thirty years, behavioral and functional imaging studies have confirmed linguistic claims concerning syntactic complexity in healthy children, in children with syntactic language impairments [24,28,29] and in healthy participants, both behaviorally and using functional imaging [30][31][32][33]. Syntactic complexity also affects verb and sentence processing in stroke-induced aphasia-an acquired language disorder often resulting from lesions within the language network [34][35][36][37]. Studies show that patients with Broca's aphasia and concomitant agrammatism are particularly affected by syntactic complexity [8,34,37,38].…”
Section: Introductionmentioning
confidence: 87%
See 4 more Smart Citations
“…Over the past thirty years, behavioral and functional imaging studies have confirmed linguistic claims concerning syntactic complexity in healthy children, in children with syntactic language impairments [24,28,29] and in healthy participants, both behaviorally and using functional imaging [30][31][32][33]. Syntactic complexity also affects verb and sentence processing in stroke-induced aphasia-an acquired language disorder often resulting from lesions within the language network [34][35][36][37]. Studies show that patients with Broca's aphasia and concomitant agrammatism are particularly affected by syntactic complexity [8,34,37,38].…”
Section: Introductionmentioning
confidence: 87%
“…The validity of the original NAVS is supported by standardization procedures and psychometric data for test validity and reliability that are provided in the respective manual. Several publications have reported the results of testing different populations and languages with the NAVS and NAT: English [8,102,103], Italian [7], and Chinese [36]. All studies have shown that both NAVS and NAT can detect and measure syntactic deficits in stroke patients and patients with primary progressive aphasia.…”
Section: The Adaptation To the German Languagementioning
confidence: 99%
See 3 more Smart Citations